Generation Z Muslims and the Qur'anic Digital Civilization: Internalizing Qur'anic Values ​​in the Era of Viral Culture - Fatahillah, Mubarok; Hafidhoh, Husnul (Sekolah Tinggi Agama Islam Kuningan, 2025)
Background:Describes the digital transformation that is changing how Generation Z Muslims consume and internalize Islamic values, creating tension between the gratification of instant viral culture and deeper spiritual understanding.Objective:States the research objectives: to investigate digital Islamic content consumption patterns, factors influencing the internalization of Quranic values, the mechanisms of viral culture, and a strategic framework for a Quranic Digital Civilization.Method:Describes the explanatory sequential mixed methods design with 800 respondents, 40 in-depth interviews, digital ethnography with 25 participants, and 15 key informants. Data analysis used SEM, multiple regression, and thematic analysis.Findings and Implications:Reveals intensive digital consumption (127.4 minutes/day), dominant platforms (TikTok, Instagram, YouTube), Religious Digital Literacy as the strongest predictor (β=0.472, p<0.001), four engagement patterns, and viral culture mechanisms that indicate opportunities and challenges. Provides an evidence-based framework for Islamic educators, digital content creators, and policymakers to optimize digital platforms in internalizing authentic values while addressing the challenges of viral culture.Conclusion:Indicates that digital platforms simultaneously present significant opportunities and structural challenges in shaping Quranic value internalization among Generation Z, necessitating a strategic, literacy-based, and value-centered approach toward building a Quranic Digital Civilization.